Distributed optical fiber sensors: what is known and what is to come - Thévenaz, Luc (Frontiers in Sensors, 2025)
This perspective article delves into the current performance limitations of distributed optical fiber sensors and proposes avenues for future advancements, as envisioned by the author, whose four-decade-long career has been dedicated to this transformative field. By upscaling the dimension of collected data, distributed sensors are essential in enabling large-scale data acquisition for “big data” systems, and optical fibers offer a unique, highly effective platform for distributed sensing. This article examines the ultimate performance achievable using state-of-the-art technologies across different sensor types. It further explores potential innovations, such as the adoption of advanced signal processing, novel fiber designs, and artificial intelligence, that could drive significant improvements in sensing performance and applications.